If then at = (A) 2(B) (C) 0(D) (E) Here's what I did:
Follow Math Help Forum on Facebook and Google+
Originally Posted by StarlitxSunshine If then at = (A) 2(B) (C) 0(D) (E) Here's what I did: ... recalculate y' ...
Ohh... Okay, so then, I get y' = -3/2 ? But that's not right...
Originally Posted by StarlitxSunshine Ohh... Okay, so then, I get y' = -3/2 ? But that's not right... your mistake (and mine) ...
Oh! >_< Wow, I can't believe I did that. x3 Thank you :33 Now, I get -4/-2, which is 2, which is (A). =)
View Tag Cloud